Adaptor protein Lnk negatively regulates the mutant MPL, MPLW515L associated with myeloproliferative disorders - Gery, Sigal (American Society of Hematology, 2007)
Recently, activating myeloproliferative leukemia virus oncogene (MPL) mutations, MPLW515L/K, were described in myeloproliferative disorder (MPD) patients. MPLW515L leads to activation of downstream signaling pathways and cytokine-independent proliferation in hematopoietic cells. The adaptor protein Lnk is a negative regulator of several cytokine receptors, including MPL. We show that overexpression of Lnk in Ba/F3-MPLW515L cells inhibits cytokine-independent growth, while suppression of Lnk in UT7-MPLW515L cells enhances proliferation. Lnk blocks the activation of Jak2, Stat3, Erk, and Akt in these cells. Furthermore, MPLW515L-expressing cells are more susceptible to Lnk inhibitory functions than their MPL wild-type (MPLWT)–expressing counterparts. Lnk associates with activated MPLWT and MPLW515L and colocalizes with the receptors at the plasma membrane. The SH2 domain of Lnk is essential for its binding and for its down-regulation of MPLWT and MPLW515L. Lnk itself is tyrosine-phosphorylated following thrombopoietin stimulation. Further elucidating the cellular pathways that attenuate MPLW515L will provide insight into the pathogenesis of MPD and could help develop specific therapeutic approaches.